Efficient BTMS for lithium-ion batteries: A study on PCM/Metal foam, heat pipe, and microchannel integration - Soheil Saeedipour; Ayat Gharehghani; Moeed Rabiei; Amin Mahmoudzadeh Andwari; Sadegh Mehranfar; Carlos Mico Reche; Navid Rabiei (Transportation Engineering)
This study introduces an innovative battery thermal management system (BTMS) that integrates liquid cooling, U-type heat pipes, and composite phase change materials (CPCM) to enhance thermal efficiency. Utilizing a transient thermo-fluid simulation model, the thermal performance of the proposed advanced BTMS for lithium-ion batteries (LIBs) is evaluated under various operational conditions. The model's predictions are validated against experimental data, ensuring reliability and robustness. The study examines two BTMS configurations: liquid cooling and a hybrid system combining active liquid cooling with passive CPCM and heat pipes. These configurations are examined under different thermal loads to assess their effectiveness. The study investigates the influence of liquid inlet velocity and ambient temperature on the maximum temperature (Tmax) and maximum temperature difference (ΔTmax) within the battery module, critical metrics affecting battery efficiency and lifespan. Additionally, the study evaluates the driving cycle and pumping power requirements, comparing the BTMS with alternative designs, demonstrating that the proposed system efficiently dissipates heat while requiring lower pumping power. Key findings include the superior performance of hybrid cooling, which reduces Tmax by 9.32 K at 293 K and maintains ΔTmax below 5 K. The hybrid BTMS achieves similar thermal performance with 53 % less power than liquid cooling. During active cooling failures, passive cooling with CPCM and heat pipes effectively removes heat, maintaining an optimal temperature range with passive BTMS peaking at 308.79 K and hybrid BTMS below 302 K. Under real-world driving conditions, the hybrid BTMS lowers Tmax by 8.2 K and stabilizes temperature fluctuations.